Current trends on visible light positioning techniques - Chaudhary, Neha (2021)
This paper presents a survey on visible light positioning techniques. The paper briefly reviews conventional positioning methods based on Rx signal strength (RSS), time difference of arrival (TDOA) and angle of arrival (AOA). Then it focus on the current research trends, relying on the machine learning techniques, sensor fusion and communication requirements.